2009
DOI: 10.2106/jbjs.i.00008
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Developmental Biology of Congenital Anomalies of the Hand and Upper Extremity

Abstract: "Classification and developmental biology of congenital anomalies of the hand and upper extremity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 83 publications
(86 reference statements)
1
27
0
7
Order By: Relevance
“…The fixed position of pronation observed in most cases was explained by Wilkie's studies [10], which showed that the forearm of the young embryo is usually in an intermediate pronation position and that the failure of segmentation makes it remain permanently in that position. In patients with unilateral synostosis such as the observation of our patient, shortening is observed in 32% of cases [11], which is very high compared the other series [4,9,12]. Functional disorders are not always correlated with the degree of fixed position of the forearm, as compensatory motion is observed with age.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The fixed position of pronation observed in most cases was explained by Wilkie's studies [10], which showed that the forearm of the young embryo is usually in an intermediate pronation position and that the failure of segmentation makes it remain permanently in that position. In patients with unilateral synostosis such as the observation of our patient, shortening is observed in 32% of cases [11], which is very high compared the other series [4,9,12]. Functional disorders are not always correlated with the degree of fixed position of the forearm, as compensatory motion is observed with age.…”
Section: Discussionmentioning
confidence: 61%
“…However, there are sporadic cases [4,5,6]. A failure of longitudinal segmentation occurring at around the seventh week of fetal development is the cause of the deformity, which is responsible for the persis-tence of a fibrous or osseous bridge between the radius and ulna, due to an abnormality of the path of the Posterior interosseous artery.…”
mentioning
confidence: 99%
“…The ideal classification system for congenital anomalies of the hand "should provide a simple description of the appearance of the hand to enhance communication between hand surgeons, and at the same time incorporate the embryological mechanism, as well as dictate the surgical reconstruction and predict the prognosis" [18]. Unlike most other classifications, our documentation system provides a simple description of either the morphological or radiographic appearance or functional status of a child's hand to facilitate communication between physicians, but it does not attempt to imply any underlying embryological causation, although it does incorporate all the previous subclassification systems.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]18 ULD is one-third to one-tenth less common than RLD. This anomaly is more common in males (3:2 ratio) and occurs bilaterally in about 25% of affected individuals.…”
Section: Etiology Of Uldmentioning
confidence: 99%